2013
DOI: 10.5539/jfr.v2n5p57
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Consumers’ Knowledge About Food Quality, Labeling and Safety in Food Choice

Abstract: <p>With the aim to investigate existence of difference between responses of selected groups of young consumers representatives toward information associated with knowledge about food quality, labeling, safety and conditions of the product use, the results of survey were analyzed crossing the groups of consumers regarding: (1) education and (2) gender, with the other variables: (i) information related to food quality, labeling and food safety; (ii) information related to food safety; (iii) information ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…We asked respondents whether they eat fruit everyday (Q6) and found that a significant number of respondents respect the principle of a healthy diet (Table 4), more affirmative answers were in P-than in S-group (Table 3) and the difference was significant ( ; p<0.05), but between M-group and F-group wasn't ( ; p0.05), as shown in Table 3. Our results confirmed the theory that researches of consumers' preference for products, may provide relevant information (Bower and Ferguson, 2008;Grujić et al, 2013b;Carr et al, 2015;Soederberg Miller and Cassady, 2015). Considerable interest respondents expressed for fruit juices consumption (Q7) and healthy eating habits (Table 4), the difference between P-and S-group answers wasn't significant ( ; p0.05), the same as between M-and F-group ( ; p0.05).…”
Section: Consumption Of Fruits Fruit Juices and Beveragessupporting
confidence: 85%
See 1 more Smart Citation
“…We asked respondents whether they eat fruit everyday (Q6) and found that a significant number of respondents respect the principle of a healthy diet (Table 4), more affirmative answers were in P-than in S-group (Table 3) and the difference was significant ( ; p<0.05), but between M-group and F-group wasn't ( ; p0.05), as shown in Table 3. Our results confirmed the theory that researches of consumers' preference for products, may provide relevant information (Bower and Ferguson, 2008;Grujić et al, 2013b;Carr et al, 2015;Soederberg Miller and Cassady, 2015). Considerable interest respondents expressed for fruit juices consumption (Q7) and healthy eating habits (Table 4), the difference between P-and S-group answers wasn't significant ( ; p0.05), the same as between M-and F-group ( ; p0.05).…”
Section: Consumption Of Fruits Fruit Juices and Beveragessupporting
confidence: 85%
“…Our analyse showed that a high percent of respondents (Table 4) confirmed interest in products with improved nutritional composition that aren't particularly nice (Q11), and the difference between adolescents and young adults answers wasn't significant ( ; p0.05), while between Mgroup and F-group was significant ( ; p<0.05). Consumer knowledge on food quality, health, and attitude to functional foods are important topics for investigation (Grunert et al, 2011;Hess et al, 2011;Nocella and Kennedy, 2012;Grujić et al, 2013aGrujić et al, , 2013bVisschers et al, 2013;Mazzocchi et al, 2014;Wansink et al, 2014). Preference for healthier functional food enriched with vitamins and minerals (Q9) expressed a relative large part of all respondents (Table 4), and difference between P-and S-group answers wasn't significant ( ; p0.05), as well as between M-and F-group ( ; p0.05) (Table 3).…”
Section: Consumption Of Fruits Fruit Juices and Beveragesmentioning
confidence: 99%
“…The perceived knowledge scale was constructed with the subjective judgement of respondents by using a Likert five-point scale: I have in depth knowledge to evaluate the quality of LM [82], Compared to an average person, I know a lot about LM [65], My friends consider me an expert in the domain of LM [65], I have heard of most of the liquid milk processing methods that are around [82], If I had to purchase LM today, I would need to gather very little information in order to make a wise decision [65]. In the final test of EFA, three questions were selected with good factor loading (see Table 3)…”
Section: Questionnaire and Measuresmentioning
confidence: 99%
“…We conducted the Kaiser-Meyer-Olkin (KMO) test and Bartlett's test of sphericity before conducting factor analysis [89]. The result of the KMO test ensured sample adequacy with a value of 0.775 (Table 2), which is well above the minimum cut value of 0.6 [82] and the result of Bartlett's test of sphericity ensured a high likelihood of the successful factorability of data [80], with a significant p-value below 0.01. The measurement model demonstrated excellent model appropriateness, with the data having χ 2 = 173.594, degree of freedom (df) = 114, p-value = 0.000, root mean square error approximation (RMSEA) = 0.027, incremental fit index (IFI) = 0.99, Tucker-Lewis index (TLI) = 0.98, comparative fit index (CFI) = 0.99, goodness of fit index (GFI) = 0.97, and χ 2 /df = 1.52.…”
Section: Measurement Modelmentioning
confidence: 99%
“…However, no differences in intentions to eat were observed in gender groups. In previous studies, differences between men and women regarding their knowledge about nutrition as well as nutritional behaviors have been reported [11,36,45,46], which is mainly explained by the greater involvement of women in providing food for the family [21,47], as well as attaching greater importance to their own appearance [48].…”
Section: Discussionmentioning
confidence: 99%